Evaluation of an Inactivated Lumpy Skin Disease Vaccine for Cattle - Zengin, Hilal; Alkaç, Zeliha Keskin; Vezir, Yaser (My University, 2023)
In the study, the efficacy of paxdoll and ndoll vaccines in Lumph Skin Disease (LSD) was investigated. Blood samples were collected from healthy, 35 calves at 6-8 months of age in Şanlıurfa province. Eight sero-negative calves were selected and sent to Ankara-Sap institute, following all the official procedures regarding internal animal’s movement. At the first stage, animals were kept at the non-contaminated facility. Animals were divided into 3 groups: First group of 3 animals were vaccinated with Poxdoll, and second group of 3 animals were vaccinated with LSD-Ndoll. 2 animals of the third group were served as a control and didn’t receive any vaccine. Blood Samples were taken on the first, 14 and 28 days of vaccination. The animals were observed for body temperature, general condition and any lesions at the vaccination site. Second stage were provided at the high containment facility where the animals at the 28th day after vaccination were moved. Each virus dilution was inoculated in 4 points at the left side and 4 at the right side. On the 14th day, the infectious doses of virus in control and vaccinated animals were calculated. Protective power of vaccines was determined by calculation of the difference between viral titer in control and vaccinated animals. As a result, sheep and goat pox vaccine of Bakrky strain at the concentration of 10 sheep doses as well Neethling vaccine provided protection against LSD, and both strains were shown to be safe for administration among cattle. In addition, no adverse reactions were observed.
Keywords: Cattle; vaccines; Lumpy skin disease; poxdoll; LSD-ndoll